Best Practices for Accelerating Healthy Environmental Policy from Organisation and Government Institutions in Indonesia - Tamaulina Sembiring; Irma Rachmawati Maruf; B.M.A.S. Anaconda Bangkara; Kholis Ernawati; Endang Fatmawati (Institute of Computer Science (IOCS), 2022)
This study discussed the escalation of healthy environmental policies by parties such as environmental organizations and the government. We designed this research in a qualitative descriptive manner where we extracted information from several sources. Then we researched it until we got an answer to finish the discussion. We examine this study under a phenomenological approach. Likewise, data analysis involves data coding, high evaluation, in-depth interpretation, and data organization. After discussing the results, we conclude, among others, that the best practices for accelerating healthy environmental policies by the government and other organizations in the country have helped publicize the government's commitment to maintaining a healthy environment, including conducting seminars, workshops by related organizations, supporting symposiums organized by the government. Other best practices are the healthy living community movement driven by the private sector and the environmental love movement to save the earth is also carried out by various non-governmental organizations, all of which want to encourage the acceleration of policies and Implementation of maintaining a healthy environment in Indonesia. It is hoped that these results will be helpful in future similar studies.